Comparison of BIPAP and SIMV+PEEP modes during weaning from mechanical ventilation after coronary artery bypass; effects on pulmonary function, ventilatory parameters and gas exchange - Karaaslan, Kazim; Talay, Fahrettin; Gülcü, Nebahat; Da?lar, Bahadir; Çolak, Cemil; Gümüş, Esra; Koço?lu, Hasan (My University, 2007)
We aimed to compare the effects of biphasic intermittant positive airway pressure (BIPAP) and synchorised intermittant mondatory ventilation (SIMV) + PEEP (positive end expiratory pressure) on pulmonary functions, gas exchange and ventilatory parameters during weaning procedure after coronary artery bypass surgery. Twenty four patients aged 30-70 years scheduling for elective cardiopulmonary bypass grefting (CABG) were included in the study. Patients were ventilated with the mode of either BIPAP (GI, n: 12) or SIMV (G2, n: 12) randomly. Five cmH2O PEEP were applied in SIMV+PEEP group. Ventilation support decreased to 4-6 min-1 according to the adequacy of spontaneous respiration, and all patients in both, groups were extubated after waiting 30 min. The spirometric measurements were performed 1 day before operation (t0), 6 hrs (t1) and 24 hrs (t2) after extubation. The decrease during t1 and t2 in FEV1 were 62 % and 58 % in G1, 56 % and 61 % in G2 respectively. During the same period of time, FVC decreased 48 % and 42 % in G1, 58 % and 52 % in G2. These differences were not statistically significant between groups. FEV1/FVC ratio was similar within and between groups. We conclude that the rise of BIPAP or SIMV+PEEP have not affected the extubation time, gas exchange and pulmonary functions during weaning after CABG.
Koroner arter baypas sonrasi mekanik ventilasyondan ayirmada BIPAP ve SIMV+PEEP yöntemlerinin ventilasyon parametreleri ile pulmoner fonksiyonlar ve gaz de?işimi üzerine etkilerinin karşilaştirilmasi
Keywords: BIPAP; Coronary artery bypass; Pulmonary functions; SIMV; Weaning